Marketing Ethics in Social Media Advertising - Handri Dian Wahyudi; Imam Mukhlis; Arief Noviarakhman Zagladi (Cita konsultindo, 2023)
Advertising constitutes one thing that is important for marketing. Advertising allows a product or firm to be recognized by consumers or society. With advertising, a firm can inform about top products firm products. Social media has also become one of the most popular advertising media today. Almost all companies have advertising content on social media. However, such corporations shall also have care in advertising that will be publicized. The firm shall have moral accountability for its advertising. Ethics requires it in advertising that constitutes fringes for corporations. Ethics is about fairness and deciding what is right or wrong, about defining the practices and rules that underpin responsible conduct between individuals and groups. In the presence of ethics in advertising, a firm has a reputation in society that eventually will be impacted by the product or service that is marketed.